Characterization of the Na(+)-Requirement in Cyanobacterial Photosynthesis - Espie, George S. (1988)
The Na(+) requirement for photosynthesis and its relationship to dissolved inorganic carbon (DIC) concentration and Li(+) concentration was examined in air-grown cells of the cyanobacterium Synechococcus leopoliensis UTEX 625 at pH 8. Analysis of the rate of photosynthesis (O(2) evolution) as a function of Na(+) concentration, at fixed DIC concentration, revealed two distinct regions to the response curve, for which half-saturation values for Na(+) (K(½)[Na(+)]) were calculated. The value of both the low and the high K(½)(Na(+)) was dependent upon extracellular DIC concentration. The low K(½)(Na(+)) decreased from 1000 micromolar at 5 micromolar DIC to 200 micromolar at 140 micromolar DIC whereas over the same DIC concentration range the high K(½)(Na(+)) decreased from 10 millimolar to 1 millimolar. The most significant increases in photosynthesis occurred in the 1 to 20 millimolar range. A fraction of total photosynthesis, however, was independent of added Na(+) and this fraction increased with increased DIC concentration. A number of factors were identified as contributing to the complexity of interaction between Na(+) and DIC concentration in the photosynthesis of Synechococcus. First, as revealed by transport studies and mass spectrometry, both CO(2) and HCO(3)(−) transport contributed to the intracellular supply of DIC and hence to photosynthesis. Second, both the CO(2) and HCO(3)(−) transport systems required Na(+), directly or indirectly, for full activity. However, micromolar levels of Na(+) were required for CO(2) transport while millimolar levels were required for HCO(3)(−) transport. These levels corresponded to those found for the low and high K(½)(Na(+)) for photosynthesis. Third, the contribution of each transport system to intracellular DIC was dependent on extracellular DIC concentration, where the contribution from CO(2) transport increased with increased DIC concentration relative to HCO(3)(−) transport. This change was reflected in a decrease in the Na(+) concentration required for maximum photosynthesis, in accord with the lower Na(+)-requirement for CO(2) transport. Lithium competitively inhibited Na(+)-stimulated photosynthesis by blocking the cells' ability to form an intracellular DIC pool through Na(+)-dependent HCO(3)(−) transport. Lithium had little effect on CO(2) transport and only a small effect on the size of the pool it generated. Thus, CO(2) transport did not require a functional HCO(3)(−) transport system for full activity. Based on these observations and the differential requirement for Na(+) in the CO(2) and HCO(3)(−) transport system, it was proposed that CO(2) and HCO(3)(−) were transported across the membrane by different transport systems.